Monitoring growth and energy utilisation of the harbour porpoise (Phocoena phocoena) in human care - Lockyer, Christina; Desportes, Geneviève; Hansen, Kirstin; Labberté, Sabrina; Siebert, Ursula (NAMMCO Scientific Publications, 2003)
Two harbour porpoises of an estimated age of 1-2 years were held in captivity from April 1997and were still alive in April 2002, after rescue from pound nets set in inner Danish waters. Theyare presently housed in an outdoor penned-off area of Kerteminde fjord. Their growth (total bodylength, girth, body weight and blubber thickness) and daily dietary intake (weight of fish, dietarycomposition and energy value) have been monitored since capture. The general activity of the animalswas regularly monitored, including two 24-hour long observation periods.Initial body weights were 37.5 kg for Eigil (male) and 40.5 kg for Freja (female). Both porpoiseslost 4 to 5 kg in the first few days because of their initial refusal to feed from the hand. Thenbody weight increased steadily reaching a peak of 44.75 kg for Eigil and 51.6 kg for Freja in earlyFebruary 1998. A fluctuation in body weight with peaks of 44 to 45 kg for the male and 51to 56kg for the female in winter followed by lows of 41 to 44 kg and 47 to 48 kg respectively in summer,established a clear pattern of seasonal fluctuation, mirrored by girth and blubber thicknessvariation. Length increased steadily from 130.5 cm to 139cm in Eigil, and from 127.5 cm to 150cm in Freja. Food intake also fluctuated seasonally, and increases in food intake preceded weightgains. Daily food consumption in Eigil and Freja represented about 7 to 9.5% of body weight.The growth of the animals resembles that of wild porpoises in the region. The sudden initial weightlosses suggested that the energy reserves of the animals may only be short-term. The large weightincrease in the winter months with colder water, correlating with the increase in girth and blubberthickness, suggest that energy reserves and blubber fat may be important for insulation.During the two 24-hour observations, the animals spent most of their time cruising around, althoughslow swimming and logging at the surface increased at night. Breathing rates were lower in theearly morning hours, consistent with diminished activity. Both animals’ movements were influencedby external activities at poolside.